ANALYSIS OF GADGET USE AND ITS IMPACT ON THE SPEAKING ABILITY OF CHILDREN AGED 1-3 YEARS (Case Study on Gadget Use in Modern Families) - Ismahani, Siti; Syafira, Syafira; Rizky, Septiana (widya balina, 2023)
The importance of the language development phase at the age of 1-3 years confirms that the influence of gadgets on children's speaking abilities is an aspect that requires special understanding and attention. The use of gadgets, if not managed wisely, has the potential to reduce the time that should be spent on direct interaction and communication between children and their environment. In this research, the literature review study method was used as the main approach to understand the impact of using gadgets on the speaking abilities of children aged 1-3 years. This approach involves analysis and synthesis of information from various literature sources relevant to the research topic. This research produces that In conclusion, this research underlines the complexity of using gadgets in children aged 1-3 years. Some children experience improvements in speaking ability through educational content, while others experience regression, especially in aspects of social interaction.